Profil Pengetahuan dan Persepsi Orang Tua terhadap Penggunaan Antibiotik pada Anak di Apotek Bangkalan: Knowledge Profile and Parent's Perception of Antibiotic Usage in Children at Bangkalan Pharmacy - April Nuraini; M. Shofwan Haris; Dianita Rahayu Rahayu; Ratri Rokhani (JURNAL FARMASI DAN MAKANAN, 2023)
Antibiotics is a major therapy in infectious diseases caused by bacteria. The use of antibiotics in children often causes problems because of abuse. The purpose of this study was to determine the profile knowledge and belief about use of antibiotics based on the theory ofHealth Belief Model. The study was conducted on the parents of pediatric patients who gets antibiotic perscription in Apotek Bamara Medika Bangkalan. This research is a cross sectional research using questionnaire tools. The analysis was done descriptively. A total of 96 respondents involved in this study, as many as 24% of male respondents and 76% of female respondents. In general knowledge of the respondents are in the category quite tend to be high. Percentage is quite 36,5% and high 31,3%. Topics of knowledge with the highest score is on the topics of rules of use and understanding of antibiotics but low on the topic of resistance. Respondents 'beliefs were derived from the perceived 4 perceived values, perceived benefit, perceived barrier, perceived threat and perceived self-efficacy. The results of the respondents' perceptions show the sufficient category with the percentage of perceived benefit 41.7%, perceived barrier 39.6%, perceived threat 66.7% and perceived self-efficacy 40.7%.